Application of neural networks in the classification of medical images textures - Dzierżak, R.; Wójcik, W. (Штучний інтелект, 2018)
Neural networks have been widely used in medical diagnostic processes. Imaging results obtained from medical devices can be analyzed in many ways. One of them is to analyze the texture of the received images. Examination of the textures of diagnostic images is based on the determination of specific parameters and characteristics of examined tissue or organ. The main goal is to assign the analyzed area to one of two basic groups: as a healthy tissue or a tissue with pathological changes. By using supervised classification and setting up a training base, it is possible to achieve 93% accuracy in classification results.